Archaeological Contributions for Cultural Tourism - Mulyantari, Enny; Erningdyah, Nuharani; Nugroho, Setyo Prasiyono; Prasetyanto, Hermawan (Technium Social Sciences Journal, 2021)
The basic concept of this research departs from the view that cultural heritage has many benefits for the interests of religion, social, education, science, technology, culture and tourism. Departing from the concept above, the problem of this research is, to what extent the contribution of archeology to tourism in this case is cultural tourism. The purpose of this study is to reveal the extent of archaeological contributions to tourism. This is important to put forward because of the assumption that tourism as a science cannot be separated from culture in this case is material culture or archeology. The method used is an explanatory qualitative approach to public relations (public relations model), which emphasizes efforts to improve the archaeological image in the eyes of the community. The results of this study reveal that archeology has a very large contribution to the development of cultural tourism.